Influence of Lactobacillus plantarum inoculation on the silage quality of intercropped Lablab purpureus and sweet sorghum grown in saline-alkaline region - Li, Huangkeyi; Wang, Tianwei; Tahir, Muhammad; Zhang, Jiaqi; Sun, Jiahao; Xia, Tianqi; Huang, Fuqing; Liu, Yayong; Liu, Zhiquan; Zhong, Jin (Frontiers in Microbiology, 2022)
Ensiling legume with cereal is an effective method to ensure the energy rich-feed, but no information is available pertaining to microbial fermentation mechanism of intercropped Lablab purpureus (Lablab) and sweet sorghum in the saline-alkaline region. Therefore, the present study investigated the silage quality and microbial community of intercropped Lablab and sweet sorghum silages grown in saline-alkaline region with or without Lactobacillus plantarum (LP) inoculation. The experimental treatments were prepared according the Lablab and sweet sorghum planting patterns: Lablab and sweet sorghum sowing seed ratios of 1:1 (L), 5:1 (M), and 9:1 (H). After harvesting, each mixture was treated with LP or sterilized water (CK), followed by 60 days of fermentation. Results showed that both LP inoculation and intercropping significantly raised the lactic acid content, and decreased the pH value, acetic acid and ammonia-N in intercropped silages. The LP addition and intercropping also improved the relative feed value by reducing structural carbohydrates. Moreover, LP silages had a greater relative abundance of Lactobacillus than CK silages, and its relative abundance increased with increased seed sowing ratio of Lablab in intercropping. The Lactobacillus plantarum was the prevalent specie in LP silages compared to CK silages, and its relative abundance also increased with increased seed sowing ratio of Lablab in intercropping. The genus Lactobacillus was negatively correlated with ammonia-N (R = -0.6, p = 0.02) and AA (R = -0.7, p < 0.01), and positively correlated with LA (R = 0.7, p < 0.01) and CP (R = 0.6, p = 0.04). Overall, the intercropped seeding ratios of Lablab and sweet sorghum ≥ 5:1 with LP inoculation resulted in better fermentation quality and preservation of nutritional components providing the theoretical support and guidance for future intercropped protein rich silage production in the saline-alkaline region.